Quantitative Risk Assessment of Salmonella in Ground Beef Products and the Resulting Impact of Risk Mitigation Strategies on Public Health - Ali J. Strickland; Fernando Sampedro; Craig W. Hedberg (Journal of Food Protection, 2023)
Salmonellosis incidence rates have not declined over the last 15 years in the US despite a significant Salmonella prevalence reduction in meat and poultry products. Ground beef is currently regulated using only qualitative Salmonella criteria, and Salmonella enumeration values have been proposed as an alternative for implementing risk-based mitigation strategies to prevent illnesses. The purpose of this study was to develop a quantitative microbial risk assessment (QMRA) model to estimate the annual number of salmonellosis cases attributable to the consumption of ground beef contaminated with Salmonella and investigate the impact of risk management strategies on public health. Model results estimated 8,980 (6,222–14,215, 90% CI) annual illnesses attributable to ground beef consumption in the US. The removal or diversion of highly contaminated ground beef production lots containing levels above 10 MPN/g (0.4%) and 1 MPN/g (2.4%) would result in a 13.6% (5,369–12,280, 90% CI) and 36.7% (3,939–8,990, 90% CI) reduction of annual salmonellosis illnesses, respectively. Frozen ground beef cooked at home was the consumption scenario of the highest risk for acquiring salmonellosis. Highly virulent serotypes accounted for 96.7% of annual illnesses despite only being present in 13.7% of ground beef samples. The removal of MDR Salmonella would result in decreased burden of disease with a 45% reduction in acute DALY annually. Focusing salmonellosis reduction efforts on removing highly contaminated ground beef lots, highly virulent Salmonella serotypes, and MDR Salmonella from not-ready-to-eat (NRTE) products were predicted to be effective risk prevention strategies.